PENGARUH ASPEK INVESTASI TERHADAP PELAPORAN CORPORATE SOCIAL RESPONSIBILITY, DENGAN BOARD MONITORING SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia sub Sektor Plastik dan Kemasan yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021) - Ulya, Safira Nuril; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
The trend of CSR reporting has become a common part of the company, in addition to completing the substance of CSR implementation activities, CSR reporting also has a significant impact on the sustainability of the company. This research was conducted to examine the effect of investment aspects on CSR reporting with board monitoring as a moderating variable. This research was conducted with the object of manufacturing companies in the basic and chemical industry sector, plastic and packaging subsectors listed on the IDX in 2019-2021. This research was conducted using Moderate Regression Analysis (MRA) which includes descriptive tests, classical assumption tests, and hypothesis testing.The results of this study show that there are two hypotheses that are influential and significant, namely on the relationship of sales growth to CSR reporting and board monitoring variables that strengthen the relationship of sales growth to CSR reporting. While the results of hypothesis testing that say there is influence but not significant is on the relationship of board monitoring that weakens the relationship of R&D intensity to CSR reporting, and board monitoring that strengthens the relationship of tangible and intangible asset growth to CSR reporting. The remaining CSR reporting variables are not influenced and not significant by the sales growth variable, the CSR reporting variable has no effect and is not significant by the R&D intensity variable, the CSR reporting variable is not influenced and not significant by the tangible and intangible asset growth variable.